Energy Audit of Lighting and Air Conditioning Systems in Baby Clothing Stores - Anis Aprilia; Ahmad Farhan; Awaludin Martin (Jurnal Teknik Mesin, 2024)
An energy audit is a method used to calculate the energy use of a building and find solutions to save energy. Things that can be achieved through this audit process are saving or reducing operational costs for business entities, industry or others, with energy savings also contributing to nature conservation and efficient use of energy which will increase the contribution to the company both financially and the lifespan of the equipment used. longer. From the analysis of the potential for energy savings through audits and conservation, it was concluded that energy use in baby clothing stores is wasteful. This can be seen based on the calculation of the Pre-Eco IKE value, which is 239.6 btu/h. After saving with the ECO option which can be done, the Post-Eco IKE value is 173.1 btu/h, where there has been a decrease in energy consumption from the wasteful category to somewhat wasteful.